Strategi Pemerintah Daerah Dalam Pengembangan Pariwisata Di Kabupaten Lembata, Provinsi Nusa Tenggara Timur - Huraq, Florianus; Supardal, Supardal (Lembaga Teewan Journal Solutions, 2026)
This study examines the strategy of the Regional Government of Lembata Regency in developing the tourism sector through the Tourism and Creative Economy Office. The analysis is based on Fred R. David's strategic management framework, covering governance, budgeting and funding, and marketing and business development strategies. A descriptive qualitative approach was employed using in-depth interviews, field observations, and document analysis of the 2023–2026 Strategic Plan of the Tourism and Creative Economy Office and relevant regulations. The findings reveal that the regional government has implemented its strategy through four main pillars: destination development, marketing and promotion, tourism human resource and creative economy development, and institutional strengthening. These efforts contributed to an increase in tourist arrivals from 12,649 in 2022 to 37,899 in 2024. Nevertheless, implementation remains constrained by inadequate infrastructure, limited tourism budget allocation, low tourism human resource capacity, insufficient private investment, and weak inter-agency coordination. The study recommends increasing tourism budget allocation, accelerating basic infrastructure development, enhancing tourism human resource capacity, expanding market access for creative economy products, and strengthening coordination among Regional Apparatus Organizations to support sustainable tourism development.